2018
DOI: 10.1021/acs.jpcc.7b12101
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Heating Plays a Dominant Role in the Plasmon-Induced Photocatalytic Reduction of 4-Nitrobenzenethiol

Abstract: It is believed that plasmon-excited electrons from Ag and Au nanostructures can induce photochemical reactions. However, the influence of heat generated by nanoparticle (NP) hotspots during light irradiation was not systematically studied yet. To evaluate the role of plasmonic heating, we performed a surface-enhanced Raman spectroscopy study of the photocatalytic conversion of 4-nitrobenzenthiol to 4-aminobenzenthiol by metal NPs with different compositions and shapes having localized surface plasmon resonance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 44 publications
0
83
0
Order By: Relevance
“…[40,41,42,47] More complicated situations have emerged from the reactions initiated from pNTP, pATP, and DMAB molecules.W here pNTP or pATPm olecules are concerned, it is reported that the LSP forms an azo bond to generate DMAB molecules; [23][24][25][26][27][28][29][30] however,other observations include reduction from pNTP to pATP, and dissociation of pNTP and the azo bond in DMAB as ac onsequence of the LSP. [24,35,56,57] Furthermore,d ifferent mechanisms were suggested even for the same chemical reaction. This confusing and chaotic situation suggests that, in some cases,m ore than two excitation mechanisms operate synergistically because the LSP serves as three excitation sources:a ne lectric field, electron-hole pairs,a nd heat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[40,41,42,47] More complicated situations have emerged from the reactions initiated from pNTP, pATP, and DMAB molecules.W here pNTP or pATPm olecules are concerned, it is reported that the LSP forms an azo bond to generate DMAB molecules; [23][24][25][26][27][28][29][30] however,other observations include reduction from pNTP to pATP, and dissociation of pNTP and the azo bond in DMAB as ac onsequence of the LSP. [24,35,56,57] Furthermore,d ifferent mechanisms were suggested even for the same chemical reaction. This confusing and chaotic situation suggests that, in some cases,m ore than two excitation mechanisms operate synergistically because the LSP serves as three excitation sources:a ne lectric field, electron-hole pairs,a nd heat.…”
Section: Discussionmentioning
confidence: 99%
“…Golubev et al concluded that local heating was crucial for plasmon-induced reduction from pNTP to pATP, which was investigated by multiwavelength and temperaturedependent SERS measurements. [57] Thel ocal heating mechanism was also applied to explain the dehydrogenation from phenyl rings in 2,13-bis(aldehyde)- [7]thiaheterohelicene molecules observed during TERS measurements. [37] Yu et al used scanning electrochemical microscopy (SECM) to investigate the effects of both the hot carriers and local heating generated by the LSP on photoelectrochemical reactions.…”
Section: Local Heating Mechanismmentioning
confidence: 99%
“…More complicated situations have emerged from the reactions initiated from p NTP, p ATP, and DMAB molecules. Where p NTP or p ATP molecules are concerned, it is reported that the LSP forms an azo bond to generate DMAB molecules; however, other observations include reduction from p NTP to p ATP, and dissociation of p NTP and the azo bond in DMAB as a consequence of the LSP . Furthermore, different mechanisms were suggested even for the same chemical reaction.…”
Section: Discussionmentioning
confidence: 95%
“…Golubev et al. concluded that local heating was crucial for plasmon‐induced reduction from p NTP to p ATP, which was investigated by multiwavelength and temperature‐dependent SERS measurements . The local heating mechanism was also applied to explain the dehydrogenation from phenyl rings in 2,13‐bis(aldehyde)‐[7]thiaheterohelicene molecules observed during TERS measurements .…”
Section: Plasmon‐induced Chemical Reactionsmentioning
confidence: 99%
“…Based on the unique features, SERS has been widely used in medical diagnosis, single molecule detection, pesticide analysis, safety inspections, and identification [7]. Notably, plasmonic metal nanomaterials (such as Ag, Au, and Cu), rough metal films, and gaps between metal surfaces and metal nanomaterials are the widely used SERS platforms for promoting photochemical reactions [8]. The molecules comprising of mostly aromatic or unsaturated bonds are generally targeted for SERS measurements.…”
Section: Introductionmentioning
confidence: 99%